Auxin Coordinates Achene and Receptacle Development During Fruit Initiation in Fragaria vesca - Tian, Yunhe; Xin, Wei; Lin, Juncheng; Ma, Jun; He, Jun; Wang, Xuhui; Xu, Tongda; Tang, Wenxin (Frontiers in Plant Science, 2022)
In strawberry, fruit set is considered as the transition from the quiescent ovary to a rapidly growing fruit. Auxin, which is produced from the fertilized ovule in achene, plays a key role in promoting the enlargement of receptacle. However, the detailed regulatory mechanisms for fruit set and the mutual regulation between achene and receptacle are largely unknown. Here, we found that pollination promoted the fruit development (both achene and receptacle), which could be simulated by exogenous auxin treatment. Interestingly, auxin was highly accumulated in achene but not in receptacle after pollination. Further transcriptome analysis showed that only a small portion of the differentially expressed genes induced by pollination overlapped with those by exogenous auxin treatment. Auxin, but not pollination, was able to activate the expression of growth-related genes especially in receptacle, which resulted in its fast growth. Meanwhile, those genes involved in the pathways of other hormones such as GA and cytokinin were also regulated by exogenous auxin treatment but not pollination. This suggested that pollination was not able to activate auxin responses in receptacles but produced auxin in fertilized achenes, and then auxin might be able to transport or transduce from achene to receptacle and promote the fast fruit growth at the early stage of fruit initiation. Our work revealed a potential coordination between achene and receptacle during fruit set, and auxin might be a key coordinator.